Integrating Thomas Lickona’s Character Education Theory with Islamic Moral Values: A Reflective Framework for Student Character Formation in Indonesia - Irfan Maulana Adnan; Dzulqarnain Hanif; Abdullah; Abdillah Fatih Fahmi (Visi Pencerah Nusantara, 2026)
This study aims to analyze Thomas Lickona’s theory of character education and its relevance to Islamic moral concepts in shaping the character of reflective students within the Indonesian educational context. The research is motivated by the growing decline in students’ morality, low social empathy, and the misuse of digital technology, which call for a more comprehensive approach to character education. The study employs a qualitative descriptive method with a library research design. Data were collected through documentation studies of scholarly works, including books, journals, academic articles, and previous research, on the concepts of moral knowing, moral feeling, and moral action within the framework of character education. The data were analyzed using content analysis techniques, including reduction, categorization, thematic presentation, and conclusion drawing. The findings indicate that Lickona’s theory offers a holistic model of character education that emphasizes not only cognitive aspects but also affective and behavioral dimensions. The integration of Lickona’s framework with Islamic moral principles, such as muhasabah (self-reflection) and tazkiyah al-nafs (self-purification), creates a reflective, contextually relevant approach to character formation aligned with national educational values and Pancasila. This integrative implementation strengthens students’ morality, empathy, and social responsibility. The study provides practical implications for educators in designing learning activities that foster moral awareness and ethical habits, as well as opening new research opportunities for applying Lickona’s theory in digital and cross-curricular contexts.